Thematic Bureaucratic Reform: Revamping the SocialWelfare Database System in Malang City - Iswanto, Denny (Badan Perencanaan Pembangunan Kota Malang, 2024)
This research aims to explore the implementation of Thematic Bureaucratic Reform, especially in the context of improving the social welfare database system in Malang City. Thematic Bureaucratic Reform is known as an approach that focuses changes and improvements to a particular sector in an effort to improve the quality of public services. Social welfare is an important aspect of development policy, and an efficient and integrated database system is the basis for supporting the planning and implementation of welfare programs. This research will analyze the challenges, potential and impact of implementing Thematic Bureaucratic Reform on improving the social welfare database system at the regional level, with a focus on Malang City. This research methodology uses qualitative data which includes analysis of policy documents and related Malang city government report documents. It is hoped that the findings of this research will provide in-depth insight into the role of database systems in supporting the effectiveness of Thematic Bureaucratic Reform, as well as potential improvements that can be implemented at the regional level. The research results show that bureaucratic reform in data base governance has been carried out with the SiBANSOS innovation. The existence of this managed system will facilitate regular data collection which can be carried out by related parties. It is hoped that this research can provide practical and strategic recommendations for strengthening the social welfare database system in Malang City, with the aim of increasing bureaucratic efficiency, increasing information accessibility, and ultimately, strengthening government efforts to improve community welfare as a whole.